Risk factors of early-onset breast cancer: A case-control study in Eastern Morocco - Bakloul, Nacer; Elaissaoui, Fouzia; Bouchefra, Said; Hammani, Khalil; Elharchli, El Hassan (Acta Biomedica Atenei Parmensis, 2026)
Background and aim: Breast cancer (BC) is the most common malignancy among women worldwide and a growing concern in low- and middle-income countries. In Morocco, BC occurs at younger ages compared to Western settings and is often aggressive, advanced at diagnosis, and associated with poorer survival. These challenges are particularly marked in Eastern Morocco, where socio-economic disparities and limited healthcare access hinder early detection. This study aimed to identify key risk factors for BC among women under 40 years old in this region. Methods: A case-control study included 140 women (70 cases with BC and 70 matched controls without cancer) recruited from the Reproductive Health Reference Center (RHRC) in Taza between 2020 and 2024. Data on sociodemographic, reproductive, gynecological, family, and behavioral factors were collected retrospectively from medical records. Logistic regression was used to estimate adjusted odds ratios (AOR) and 95% confidence intervals (CI). Results: The mean age was similar between cases (33.7 ± 5.2 years) and controls (34.5 ± 3.7 years). Early menarche (< 12 years) was strongly associated with increased BC risk (AOR = 5.70; 95% CI: 1.40–23.24). Late first pregnancy (≥ 35 years) also significantly elevated risk (AOR = 5.01; 95% CI: 1.32–18.95). A positive family history of BC emerged as an independent predictor (AOR = 3.92; 95% CI: 1.71–8.95). In contrast, parity showed a protective effect (AOR = 0.31; 95% CI: 0.10–0.95), while oral contraceptive use demonstrated non-significant trends. No participant reported tobacco or alcohol use. Conclusion: Early menarche, late first pregnancy, and family history are major risk factors for early-onset BC in Eastern Morocco, whereas parity appears protective. These findings highlight the importance of culturally adapted prevention and early detection strategies.